Metoda Kualitatif Untuk Penelitian Kesehatan Lingkungan - Agus Kharmayana Rubaya (Sanitasi: Jurnal Kesehatan Lingkungan, 2016)
The application of qualitative research methods in health-related areas is showing an increasing trend. Because the method is ontologically and epistemologically different, the results obtained can compliment, complete and enrich the results obtained from quantitative method that is usual-ly employed in health sciences. In environmental health area, qualitative study, for instance can explore perception of stakeholders about environmental risk factors or about environmental ha-zards in the community based on their point of views. There are some conditions of which quali-tative study is more appropriate, e.g. to gain new perspective about a problem, and to explore a problem with only limited knowledge is revealed. Same with quantitative research, in its applica-tion, qualitative research have to pay attention on ethical issues, and the validity, reliability, and generalisability of the studies.